Shaping the professional landscape through research, advocacy and education – an Australian perspective. (6th April 2017) - Siemensma, Gemma; Ritchie, Ann; Lewis, Suzanne
Abstract: This article is the first in a new series in this regular feature. The intention of the series is to look at important global developments in health science libraries. Librarians will be invited to share with HILJ readers key initiatives in their country or region. These articles should serve as a road map, describing the key changes in the field and exploring factors driving these changes. We initiate this series with an article by three Australian librarians who use research findings to depict the evolving professional landscape in their country. The starting point of their analysis is a report completed in 2011 which looked into likely future workforce and education requirements for health library professionals. The authors trace the achievements since then, most notably in the areas of research, advocacy and education. Clearly, a great deal has been achieved leading to a greater return on investment. The authors maintain that the key to shaping the profession and enhancing the status of librarians is ongoing professional development. To this end, Australia is promoting a systematic, competency based health specialist certification. Finally, they identify trends impacting on health librarianship, such as the growing importance of research data management and consumer health literacy. JM